2015
DOI: 10.1161/circulationaha.114.015064
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dimethylarginine Dimethylaminohydrolase 1 Is an Important Regulator of Angiogenesis but Does Not Regulate Vascular Reactivity or Hemodynamic Homeostasis

Abstract: Clinical Perspective on p 2225In healthy individuals, plasma ADMA concentrations are maintained at ≈0.5μmol/L through a combination of enzymatic breakdown and renal excretion that account for ≈80% and ≈20% of clearance, respectively.10 Asymmetrical methylarginines are metabolized by the action of dimethylarginine Background-Asymmetrical dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthesis and a risk factor for cardiovascular disease. Dimethylarginine dimethylaminohydrolase (DDAH) enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 39 publications
(54 reference statements)
3
31
0
Order By: Relevance
“…However, chronic accumulation of ADMA in global DDAH1 KO causes reduced vascular NO production, moderate hypertension, and diminished acetylcholine-induced vasodilatation [16, 23]. ADMA accumulation in global DDAH1 KO mice or endothelial specific DDAH1 KO mice also results in reduced angiogenesis and impaired vascular injury repair capacity [11, 39, 40]. Conversely, over-expression of DDAH1 results in decreases of plasma and tissue ADMA levels, which was associated decrease of systemic blood pressure [10], increase of insulin sensitivity [35], increase of angiogenesis [19], and reduced high fat diet induced atherosclerosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, chronic accumulation of ADMA in global DDAH1 KO causes reduced vascular NO production, moderate hypertension, and diminished acetylcholine-induced vasodilatation [16, 23]. ADMA accumulation in global DDAH1 KO mice or endothelial specific DDAH1 KO mice also results in reduced angiogenesis and impaired vascular injury repair capacity [11, 39, 40]. Conversely, over-expression of DDAH1 results in decreases of plasma and tissue ADMA levels, which was associated decrease of systemic blood pressure [10], increase of insulin sensitivity [35], increase of angiogenesis [19], and reduced high fat diet induced atherosclerosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DDAH1 gene deficiency causes increases of plasma and tissue ADMA and L-NMMA, which is associated with reduced NO production, moderate hypertension, and endothelial dysfunction (43,44,63). DDAH1 gene deficiency also limits angiogenesis and impairs vascular injury repair (30,113,115). Conversely, over-expression of DDAH1 results in decreases of plasma and tissue ADMA levels, which was associated decrease of systemic blood pressure (28), increase of insulin sensitivity (94), increase of angiogenesis (53,113,115), reduced high fat diet induced atherosclerosis (52,108) and graft coronary artery disease (98).…”
Section: The Important Role Of Ddah1 In Cardiovascular Functionmentioning
confidence: 99%
“…Using the Tie-2 Cre system, we found that endothelial specific DDAH1 gene deletion caused significant decreases of DDAH1 in vascular tissues, increased tissue and plasma ADMA, reduced acetylcholine induced NO production and vessel dilatation, and resulted in systemic hypertension (43,44), abnormal angiogenesis, and impaired endothelial injury repair (113,115). However, using a similar Tie-2 Cre system, a new endothelial specific DDAH1 strain was shown to have no major effect on systemic ADMA content (30), but significantly attenuated angiogenesis (30). While endothelial specific DDAH1 gene deletion using Tie-2 Cre system attenuated endothelial injury repairs and angiogenesis in both mouse strains, the effect of endothelial DDAH1 gene deletion on systemic blood ADMA was different in these mouse strains.…”
Section: The Important Role Of Ddah1 In Cardiovascular Functionmentioning
confidence: 99%
“…; Dowsett et al. ). DDAH1/ADMA/NOS pathway regulation of caspase‐3 mediated apoptosis has been described (Wang et al.…”
Section: Introductionmentioning
confidence: 98%
“…In a variety of vascular diseases, decreased DDAH expression/activity is associated with endothelial dysfunction mediated by increased levels of ADMA causing inhibition of eNOS (Pope et al 2009a). Endothelial DDAH1-specific knockout mice have impaired angiogenesis (Zhang et al 2013;Dowsett et al 2015). DDAH1/ADMA/NOS pathway regulation of caspase-3 mediated apoptosis has been described (Wang et al 2016;Hou et al 2018;Liu et al 2018), and DDAH1 upregulation has been associated with tumor regression in a xenograft mouse model (Yung et al 2016).…”
Section: Introductionmentioning
confidence: 99%